Influence Of The Philosophers Ideas On Teaching Arabic In Light Of (Al-Tamayz) Al-Firharwi/ ØªØ£Ø«ÙŠØ±Ø£ÙÙƒØ§Ø± Ø§Ù„ÙÙ„Ø§Ø³ÙØ© Ø¹Ù„Ù‰ ØªØ¯Ø±ÛŒØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø¶ÙˆØ¡ ((Ø§Ù„ØªÙ…ÙŠØ²)) Ù„Ù„ÙØ±Ù‡Ø§Ø±ÙˆÙŠ - Saeed Rana, Hafiz Ahmed; Khalil, Abuzar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The rise of philosophy has coalesced with the start of the world, which means a